Hugh MacDiarmid - Morgan, Edwin, 1920-2010 (Writers and Their Work Series., 1976)
C.M. Grieve, or 'Hugh MacDiarmid' as he is best known, has written under both names, and in this he seems to be following a Scottish custom (one could instance 'Lewis Grassic Gibbon') and J. Leslie Mitchell, or 'James Bridie' and O.H. Mavor). But whether two, or more than two identities meet in his work, there is no doubt that he is one of the most far-ranging, original, and remarkable poets of his time. Apart from his natural abilities, and the recogniza.